Wastewater Treatment by Adsorption and/or Ion-Exchange Processes for Resource Recovery - Vecino, Xanel; Reig, Mònica (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The triple-R model (reduce, reuse, and recycle) is the essential concept of the circular economy. Due to population growth, the recovery of added-value products from wastes has become a challenge. Wastewaters of different origin (urban, industrial, mining, textile, distillery, and microbial culture, among others) are rich in energy, water, and nutrient sources that can be recovered and reused within a circular economy framework. Recently, wastewater treatment plants have been converted into biofactories, since they can convert waste into new products (water, nutrients, fertilizers, biomethane, electricity, heat, etc.) with a minimal environmental impact. In this context, adsorption and ion-exchange, as well as the integration of both processes, have been proposed as promising technologies for the treatment of wastewaters for resource recovery. Therefore, the aim of this Special Issue, entitled "Wastewater Treatment by Adsorption and/or Ion-Exchange Processes for Resource Recovery", is to promote these two processes as innovative and environmentally friendly alternatives for the recovery of secondary raw materials from by-products or waste streams. These processes could improve the environmental, economic, and social impacts of the currently used wastewater treatment techniques.